2017
DOI: 10.1371/journal.pone.0178871
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of a mandatory pre-abortion ultrasound viewing law: A mixed methods study

Abstract: BackgroundSince mid-2013, Wisconsin abortion providers have been legally required to display and describe pre-abortion ultrasound images. We aimed to understand the impact of this law.MethodsWe used a mixed-methods study design at an abortion facility in Wisconsin. We abstracted data from medical charts one year before the law to one year after and used multivariable models, mediation/moderation analysis, and interrupted time series to assess the impact of the law, viewing, and decision certainty on likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…By women's reports, the decision to continue the pregnancy after visiting an abortion clinic was typically influenced by structural and material barriers in Louisiana and by women's own decisions in Maryland. The fact that we did not find a large number of women by recruiting from prenatal care who had decided to continue a pregnancy after visiting an abortion clinic is consistent with previous research that has found that few women who attend a mandatory abortion information visit or attend the abortion appointment decide to continue the pregnancy and that those who do were typically conflicted about their decision when they presented for care (Cameron & Glasier, 2013;Gatter, Kimport, Foster, Weitz, & Upadhyay, 2014;Roberts et al, 2016;Upadhyay et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…By women's reports, the decision to continue the pregnancy after visiting an abortion clinic was typically influenced by structural and material barriers in Louisiana and by women's own decisions in Maryland. The fact that we did not find a large number of women by recruiting from prenatal care who had decided to continue a pregnancy after visiting an abortion clinic is consistent with previous research that has found that few women who attend a mandatory abortion information visit or attend the abortion appointment decide to continue the pregnancy and that those who do were typically conflicted about their decision when they presented for care (Cameron & Glasier, 2013;Gatter, Kimport, Foster, Weitz, & Upadhyay, 2014;Roberts et al, 2016;Upadhyay et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…They were not policies targeting women's decision-making. This pattern of findings is consistent with extant literature that indicates that the restrictions that create financial and logistical barriers to abortion care-such as restrictions on Medicaid funding for abortion, gestational age limits, and two in-person-visit requirements-limit women's ability to obtain an abortion, whereas laws targeting women's decision-making-such as mandatory ultrasound viewing and waiting periodsmostly do not (Cook, Parnell, Moore, & Pagnini, 1999;Hajri, Raifman, Gerdts, Baum, & Foster, 2015;Joyce et al, 2009;Puri et al, 2015;Roberts et al, 2016;Upadhyay et al, 2017;Upadhyay, Weitz, Jones, Barar, & Foster, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations